An FBG based smart clamp for the detection of incipient clamp looseness in industrial piping system. (July 2019) - Wang, Zechao; Liu, Mingyao; Zhou, Zude; Qu, Yongzhi; Wei, Qin; Hong, Liu; Yang, Feng
Highlights: The smart clamp with FBG sensing technology is presented in this work for the first time. The analytical model and FEM are developed to derive the measuring principle and optimize the structure of the clamp. A practical application, i.e. the incipient clamp looseness detection for an industrial piping system, is further conducted. Abstract: Distributed block clamps are widely used in hydraulic piping systems. However, due to wear and tear over time, the clamps may loosen, and if not detected in the early stages, it can lead to the catastrophic results. The common methods to detect the clamp looseness are based on the monitoring the pre-load of the connected bolts. The Fiber Bragg Grating (FBG) sensors, as the emerging sensing technology with anti-electromagnetic interference, small size and lightweight, easy to install, corrosion resistant, durable, cost effective and multiplexed properties has been used to design smart bolts and smart washers in the existed literatures recently. However, the distributed features of the smart bolts are limited to the through-hole structures and the smart washer can only be used to the bolted connections with big-diameter bolts, which makes the smart bolts and washers difficult to apply to distributed clamp bolted with small-diameter bolts. Therefore, an FBG based smart clamp is presented for the first time in this paper. The theoretical models, i.e. the analytical model and Finite Element Model (FEM) are developed to derive the measurement principle and optimize the structure of the clamp. The calibration experiments of the smart clamp are conducted to obtain the sensitivity of the smart clamp. Subsequently, a practical application, i.e. clamp looseness detection, is given in an industrial piping system which shows that the smart clamp is high sensitive to the incipient looseness of the clamp.